Nursing practices in the family health strategy in Brazil: interfaces with illness - Mariana Mendes; Letícia de Lima Trindade; Denise Elvira Pires de Pires; Maria Manuela Ferreira Pereira da Silva Martins; Olga Maria Pimenta Lopes Ribeiro; Elaine Cristina Novatzki Forte; Jacks Soratto (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To identify Nursing practices in the Family Health Strategy in Brazil and interfaces in the illness of these professionals. Method Qualitative research, carried out in the five Regions of Brazil, with 79 nursing professionals from 20 health units. Data were collected from 2015 to 2017, using interviews, observation and documentary study. The analysis with the aid of the software ATLAS.ti 8.0, guided by the theorization of the Work Process and Workloads. Results The practices of the care dimension prevailed, followed by the administrative-managerial and educational dimensions. The illness resulting from workloads, predominantly psychic, was related to care practices, potentiated by overload and poor working conditions. Conclusion The centrality of nursing practices in the dimension of care and administrative management characterized the professional work in Primary Care. The findings indicate that improved working conditions may minimize the wear and tear of these professionals in this scenario.